Preparation of Biochar with Palm Oil Mill Sludge by using Microwave for Copper Removal - Lee, Yan Bin (2015)
This study aims to prepare the bio-char from residues of palm oil mill sludge (POMS) after anaerobic digestion system through microwave pyrolysis method to remove copper. The two main parameters i.e. temperature, and holding time for the bio-char production were investigated to produce the bio-char. Results obtained were interpreted by response surface methodology. Properties of palm oil mill sludge, biochar produced at 4, 6, 8, 10, and 12 minutes were determined in term of various functional groups. The optimum conditions for preparing bio-char from palm oil mill sludge were found to be 300 watts and 10 minutes, the maximum removal efficiency of the optimized POMS bio-char is 83%.